"Give Me Some Wiggle Room": How to Feel at Home in the Gap between Design, Building and Decay. Issue 1 (2nd January 2019) - Decroos, Bart; Schrijver, Lara
Abstract: This article takes the Caritas building by De Vylder Vinck Taillieu (2016) as a foil to discuss tolerance from a number of perspectives, demonstrating the productive nature of the very notion of tolerance as a filter through which to understand a contemporary building with an innovative approach to professional conventions in both psychiatric care and architecture. The building, a pavilion on the campus of a psychiatric care facility in Belgium, flies in the face of architectural conventions for care facilities, yet provokes a rethinking of contemporary institutional care. Its strategic use of the gap between idea and building and of improvization in the building process provide a striking example of the potential ripple effects from a singular project that provide "wiggle room" in order to understand what architecture can do.